Compliance Status of Smoke-Free Public Places Law in Nepal - Aditya Shakya; Bhakta Bahadur KC; Rasmita Shrestha (Advances in Public Health)
Background. The tobacco epidemic is one of the biggest public health threats the world has ever faced, killing around 8 million people a year. The tobacco control program has been one of the priority programs in Nepal but still satisfactory results have not been achieved yet. The main objective of this study was to assess the tobacco smoke-free law compliance in public places of the provincial headquarters of Nepal. Materials and Methods. A cross-sectional observational study was conducted in 2019 in 560 public places of seven provincial headquarters of Nepal. Convinent samples were collected from at least three different clusters (wards) of each city. Indoor and outdoor locations of public places were observed. Observation tool was adopted from the Guide for Conducting Compliance Studies (John Hopkins School of Public Health). Data were entered in Epi Datav3.1, and analysis was done using IBM SPSS 26. Results. This study showed less use of no-tobacco signage which was 32% in the indoor areas and 13% in the outdoor areas in public places but they were placed in visible areas. Tobacco use in public places is still prevalent and it was higher (40%) in outdoor of public places. Three-fourths (76%) of public places was observed for buying and selling tobacco products within their 100 m premises. Tourist hotels, public toilets, and bus stops/ticket counters had low tobacco law compliance both in indoor and outdoor areas. Though public vehicles and cinema halls had high tobacco law compliance in indoor areas, law compliance in outdoor areas was low. Province-wise comparison showed that there was a similar pattern of tobacco law compliance in the indoor areas but outdoor law compliance was low in Madesh, Bagmati, and Karnali province. Conclusion. It is evident that while progress has been made in certain aspects of tobacco law compliance, there remains a compelling need for comprehensive and targeted interventions to ensure adherence to laws in public places across the country.